2007
DOI: 10.1073/pnas.0607177104
|View full text |Cite
|
Sign up to set email alerts
|

Developmental hearing loss eliminates long-term potentiation in the auditory cortex

Abstract: Severe hearing loss during early development is associated with deficits in speech and language acquisition. Although functional studies have shown a deafness-induced alteration of synaptic strength, it is not known whether long-term synaptic plasticity depends on auditory experience. In this study, sensorineural hearing loss (SNHL) was induced surgically in developing gerbils at postnatal day 10, and excitatory synaptic plasticity was examined subsequently in a brain slice preparation that preserves the thala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…Kamke et al (2005) recently demonstrated that cholinergic input to adult cat AI from the basal forebrain, essential for behaviorally-conditioned plasticity (e.g., Bakin and Weinberger, 1996), is not essential for lesion-induced plasticity, though this does not rule out potential top-down habituation in our experiments. Perhaps the immaturity in developing animals of fundamental neural processes such as GABA-ergic inhibition and synaptic depression (e.g., Kotak et al, 2007Kotak et al, , 2008Sanes and Walsh, 1998) can account for the above paradox, especially in light of recent revelations about their importance to the mechanisms of cortical plasticity (Maffei et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Kamke et al (2005) recently demonstrated that cholinergic input to adult cat AI from the basal forebrain, essential for behaviorally-conditioned plasticity (e.g., Bakin and Weinberger, 1996), is not essential for lesion-induced plasticity, though this does not rule out potential top-down habituation in our experiments. Perhaps the immaturity in developing animals of fundamental neural processes such as GABA-ergic inhibition and synaptic depression (e.g., Kotak et al, 2007Kotak et al, , 2008Sanes and Walsh, 1998) can account for the above paradox, especially in light of recent revelations about their importance to the mechanisms of cortical plasticity (Maffei et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, the gerbil has become a highly valuable animal model for auditory (for some overview see Budinger and Klump, 2008), visual (Ellard, 1998;Fite et al, 2003), other sensory (Vallejo et al, 2000;Hwang et al, 2008) and multisensory studies (Cahill et al, 1996;Budinger et al, 2006). It is also successfully used for investigations on brain development, aging and disease (Cheal, 1986;Stuermer and Scheich, 2000;Gleich et al, 2007;Kotak et al, 2007), behaviour (e.g., sound localization: Maier and Klump, 2006;Siveke et al, 2008), learning and memory mechanisms Schicknick et al, 2008).…”
Section: The Mongolian Gerbil As a Model For Auditory Multisensory Amentioning
confidence: 98%
“…This is because LTP not only is considered as the underlying mechanism of long-term synaptic plasticity and memory but also plays an important role in the diagnosis of neural plasticity diseases [20]. The pathologic alterations of LTP contribute to a number of neurological diseases, including depression, Parkinson's disease, epilepsy, and neuropathic pain.…”
Section: Stimulationmentioning
confidence: 99%